2020
DOI: 10.3991/ijim.v14i06.13405
|View full text |Cite
|
Sign up to set email alerts
|

Development of SMASH Skills Training Model on Volleyball Based on Interactive Multimedia

Abstract: <p class="0keywords"><strong>—</strong><em> </em>SMASH's skill is a technique that can be done by a person in a hard swooping towards your opponent to produce numbers. Interactive multimedia technology is expected to be a guideline for athletes in looking at more variation models of SMASH. The aim of development research is to produce an interactive multimedia volleyball playing skill training model. The method used in this research is development research design by Borg and Gall.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
8
Order By: Relevance
“…Based on these results, it can be concluded that push-up training has a significant effect on improving the smash skills of Club Permata's men's volleyball players. The result previous research on exercise improve vvolleyball smash skils [15]. Research result volleyball fundamental skills training [16].…”
Section: Discousionmentioning
confidence: 92%
“…Based on these results, it can be concluded that push-up training has a significant effect on improving the smash skills of Club Permata's men's volleyball players. The result previous research on exercise improve vvolleyball smash skils [15]. Research result volleyball fundamental skills training [16].…”
Section: Discousionmentioning
confidence: 92%
“…Faktor perkembangan jasmani anak merupakan prioritas utama dalam mengoptimalkan gerak anak. Teknik dasar bola voli merupakan faktor yang sangat penting karena itu mempengaruhi kelancaran permainan, bukan hanya prestasi (Suhairi, Asmawi, Tangkudung, Hanif, & Dlis, 2020). Mengingat anak dalam masa pertumbuhan dan perkembangannya memiliki kekhususan baik pada proses pertumbuhannya maupun secara kejiwaannya.…”
Section: Pendahuluanunclassified
“…In volleyball, vertical jumps require coordination of the muscles of the legs, arms and trunk [8][9]. Several components of conditions such as explosive power, strength, flexibility, and endurance are parameters to determine performance in volleyball [10] [11]. Phenomenon Currently, instrumentation and measurement of volleyball skills are still done manually and by using a test to do smash repeatedly using a mat or a line made in the field [12].…”
Section: Introductionmentioning
confidence: 99%